MANAJEMEN PENDIDIKAN ANAK DALAM AJARAN HINDU KAHARINGAN DI KALIMANTAN TENGAH - ayu juniarthi (Satya Sastraharing : Jurnal Manajemen, 2019)
Abstract In the era of globalization, management of education is a factor that really needs attention from various parties in order to improve the quality of education. Management of Education for children is an effort as a form of parental, community, and government responsibility, which starts from the smallest scope, namely the family environment. Management of Education for children is closely related to figures who have a central role, namely parents (father and mother) as educators who are first, foremost for children and close to children. Hindu Kaharingan teachings have their own concepts related to the management of children's education which are important given early on so that children can grow up to have good character and character. Keywords: Management of Education for children, Hindu Kaharingan, Panaturan